PENGARUH PENGGUNAAN MEDIA SOSIAL DAN LITERASI DIGITAL TERHADAP PERILAKU CYBERBBULLYING PADA SISWA KELAS XI PEMASARAN SMKN 1 MEDAN - Tessa Rifka Simarmata; Aurora Elise Putriku (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of social media use and digital literacy on cyberbullying behavior among eleventh-grade Marketing students at SMKN 1 Medan. This research employed a quantitative approach using an ex-post facto research design. The study population consisted of 63 students, all of whom were selected as the research sample using the total sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 25. Prior to hypothesis testing, classical assumption tests were performed, including normality, linearity, and multicollinearity tests. The findings indicate that social media use has a positive and significant effect on cyberbullying behavior among eleventh-grade Marketing students at SMKN 1 Medan. Digital literacy also has a significant effect on cyberbullying behavior. Furthermore, social media use and digital literacy simultaneously have a significant effect on cyberbullying behavior. These findings suggest that intensive social media use without adequate digital literacy skills may increase students' tendency to engage in cyberbullying behavior. Therefore, collaborative efforts involving schools, parents, and other stakeholders are needed to enhance students' digital literacy, strengthen ethical behavior in social media use, and foster responsible digital citizenship in order to minimize cyberbullying behavior within the school environment.